2022
DOI: 10.2166/wpt.2022.070
|View full text |Cite
|
Sign up to set email alerts
|

Impact of irrigation with Lake Abaya water on soil quality – southern Rift Valley, Ethiopia

Abstract: The study's aim was to assess the impact of using water from Lake Abaya for irrigation and its impact on soil quality at Mirab Abaya, Ethiopia. Six water samples from the edge of Lake Abaya and 30 (18 irrigated and 12 rain-fed) composite soil samples from farm lands in Wajifo, Fura and Algae were collected. Analyses showed that the use of water from Lake Abaya will bring a soil salinity hazard in future. The soil analyses showed variations in space and time in the physico-chemical components in the study area.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The results indicated that soil leaching was an effective method to decrease high salt concentrations to levels, which are suitable for the production of semi-tolerant and tolerant crop plants (Setegn et al 2022). Accordingly, with increasing soil depth the effectiveness of soil leaching decreased, however, interestingly the leaching method was able to decrease salt in the soil to the depth of 125 cm, which is a suitable depth for the growth of most crop roots.…”
Section: Discussionmentioning
confidence: 96%
“…The results indicated that soil leaching was an effective method to decrease high salt concentrations to levels, which are suitable for the production of semi-tolerant and tolerant crop plants (Setegn et al 2022). Accordingly, with increasing soil depth the effectiveness of soil leaching decreased, however, interestingly the leaching method was able to decrease salt in the soil to the depth of 125 cm, which is a suitable depth for the growth of most crop roots.…”
Section: Discussionmentioning
confidence: 96%